Investigation of the Strength Properties of Frozen Soils. Fiscal Year 1952. Report of Investigations. Volume 1. - ARCTIC CONSTRUCTION AND FROST EFFECTS LAB BOSTON MASS (1953)
The report contains the data obtained during the second consecutive year of investigational laboratory work on the strength properties of frozen soils. It is a continuation and extension of the investigational program initiated in Fiscal Year 1951 and reported fully in SIPRE Report 8, 'Investigation of Description, Classification, and Strength Properties of Frozen Soils, Fiscal Year 1951', dated June 1952. (Author) See also Volume 2, AD-712 651.